FIN-TECH, FINANCIAL INCLUSION, AND SUSTAINABILITY: A QUANTITATIVE APPROACH OF MUSLIMS SMEs - Nurohman, Yulfan Arif; Kusuma, Melia; Narulitasari, Devi (IJIBE (International Journal of Islamic Business Ethics), 2021)
Sustainability of Small and Medium Enterprises (SMEs) is very important to be noted or observed. Because the majority of Indonesia’s population is Muslim and many of them are SMEs Actors. This study aim to provide empiric proves about the relation among financial technology (Fintech), financial inclusion, and sustainability muslims SMEs in Solo Raya area. This study uses quantitative approach. Analysis instrument used in this study is Partial Least Square (PLS). All data in the study are collected by handing out questionnaires to 96 SMEs owners who are Muslim chosen with accidental sampling technique. The result of this study shows that there is a positive relation between financial technology and financial inclusion. Financial technology also have positive relation toward the sustainability of SMEs. Besides that, financial inclusion also have positive relation with the sustainability of SMEs. With these results, it is expected that could give more viewpoint to the Government to give a convenient access and support the existence and sustainability of SMEs